2014
DOI: 10.5772/58248
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Lane Detection on Suburban Streets Using Visual Cue Integration

Abstract: The detection of lane boundaries on suburban streets using images obtained from video constitutes a challenging task. This is mainly due to the difficulties associated with estimating the complex geometric structure of lane boundaries, the quality of lane markings as a result of wear, occlusions by traffic, and shadows caused by road-side trees and structures. Most of the existing techniques for lane boundary detection employ a single visual cue and will only work under certain conditions and where there are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Similarly, certain distinctive test data-sets have been evaluated over different hyper-parameters to obtain the over-all accuracy of the model and the results had been tabulated in Table.I. We observed a significant improvement in the results in comparison to the existing methods like SVM, MLPC, as shown in Fig.6 and a few other adaptive algorithms, as in [1], [2].…”
Section: Performance Evaluationmentioning
confidence: 54%
See 1 more Smart Citation
“…Similarly, certain distinctive test data-sets have been evaluated over different hyper-parameters to obtain the over-all accuracy of the model and the results had been tabulated in Table.I. We observed a significant improvement in the results in comparison to the existing methods like SVM, MLPC, as shown in Fig.6 and a few other adaptive algorithms, as in [1], [2].…”
Section: Performance Evaluationmentioning
confidence: 54%
“…The retrieval of images from Google Street-View is quite a powerful alternative rather than camera-based images in certain applications like drawing out the coverage of plantation in a region or detecting traffic signs/figures on the lane and take steps to improve the awareness. Mainly for the earlier stages of development huge image data-sets are available for many different countries all over the world (2) which can be accessed easily and efciently for further developments on them as depicted in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Many approaches for automatic lane detection have been reported in the literature: (Assidiq 2008), (Fernando 2014), (Saha 2012), (Van Winden 2016) and (Wang 2006), to mention a few.…”
Section: Introductionmentioning
confidence: 99%
“…They show that their proposal is robust to light changes and shadows by testing it with both painted and unpainted road as well as curved and straight road in different weather conditions. In (Fernando 2014), the authors face lane detection by integrating two visual cues: 1) stripe-like features found on lane lines extracted using a two-dimensional symmetric Gabor filter, and 2) texture characteristic determined using the entropy measure of a predefined neighbourhood around a lane boundary line. They integrate both visual cues using a rule-based classifier which incorporates a modified sequential covering algorithm to improve robustness.…”
Section: Introductionmentioning
confidence: 99%
“…Vários são os algoritmos propostos para detecção de pavimentos Birdal e Erçil (2007), Assidiq et al (2008), Yenikaya, Yenikaya e Düven (2013), Fernando et al (2014), Yinka et al (2014), entretanto, a maior parte dos algoritmos encontrados está focada na localização do pavimento a partir de lasers ou imagens obtidas a partir de câmeras instaladas em veículos terrestres, mais especi camente, para o uso em veículos terrestres autônomos. Esses algoritmos não funcionam quando se tem imagens obtidas a partir de veículos aéreos, uma vez que as informações da trajetória e dos ângulos utilizados não serem os mesmos.…”
Section: Uso De Veículos Aéreos Para Detecção De Defeitos Em Pavimentunclassified